Riesgo de desarrollar úlceras de los pies en pacientes diabéticos que reciben programa educativo vs los que no lo reciben, en el Hospital Teófilo Dávila. - Zúñiga Silva, Wilson P. (2012)
Using a cross-sectional, descriptive, cases and controls were studied 50 diabetic patients receiving educational program (club diabetics) and 50 patients not receiving educational program (outpatient) in Teófilo Dávila Hospital in the city of Machala in the year 2011, using the risk assessment from of foot ulceration and amputation in diabetic patients, performing a baseline data, whose overall objective is to establish the risk of developing foot ulcers in diabetic patients receiving educational program and those who are not receive and how to identify specific individual characteristics (age and gender) determine years of diabetes and identify risk factors present such patients.